Geographical dynamics and firm spatial strategy in China - Zhu, Shengjun; Pickles, John, 1952-; He, Canfei (Springer geography., 2017)
This book offers the first detailed account of the complex geographical dynamics currently restructuring China?s export-oriented industries. The topics covered are relevant to post-socialist geography, development studies, economics, economic sociology and international studies. It offers academics, international researchers, postgraduate and advanced undergraduate students in these fields an accessible, grounded, yet theoretically sophisticated account of the geographies of global production networks, value chains, and regional development in developing countries and emerging economies. It is of particular interest to economic geographers and economic sociologists involved in the growing debates over local clusters, embeddedness, global sourcing and global production, and over the global value chain/global production network. It also appeals to national policymakers, since it directly addresses economic and industrial policy issues, such as industrial competitiveness, regional and national development, industrial and employment restructuring and trade regulation.